2010
DOI: 10.1017/s1751731110000595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental pollutants on the reproduction and welfare of ruminants

Abstract: Anthropogenic pollutants comprise a wide range of synthetic organic compounds and heavy metals, which are dispersed throughout the environment, usually at low concentrations. Exposure of ruminants, as for all other animals, is unavoidable and while the levels of exposure to most chemicals are usually too low to induce any physiological effects, combinations of pollutants can act additively or synergistically to perturb multiple physiological systems at all ages but particularly in the developing foetus. In she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 157 publications
1
45
0
Order By: Relevance
“…This suggests that imprinted genes may serve as candidate loci harbouring potentially important DNA sequence polymorphisms contributing to heritable variation in livestock performance traits--a hypothesis that is supported by a number of recent genotype-phenotype association studies performed in domestic livestock populations [8,21,22,24,26,27,62]. In this study, significant phenotypic associations ( P ≤ 0.05) were detected between SNPs located proximal to or within six of the eight candidate bovine imprinted genes analysed-- CALCR , GRB10 , PEG3 , RASGRF1 , ZIM2 , and ZNF215-- and range of cattle performance traits; significant associations ( P ≤ 0.05) were not observed between performance traits and SNPs within the PHLDA2 and TSPAN32 genes, although one SNP within the bovine TSPAN32 gene showed a tendency to be associated ( P ≤ 0.10) with a number of the performance traits assessed.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that imprinted genes may serve as candidate loci harbouring potentially important DNA sequence polymorphisms contributing to heritable variation in livestock performance traits--a hypothesis that is supported by a number of recent genotype-phenotype association studies performed in domestic livestock populations [8,21,22,24,26,27,62]. In this study, significant phenotypic associations ( P ≤ 0.05) were detected between SNPs located proximal to or within six of the eight candidate bovine imprinted genes analysed-- CALCR , GRB10 , PEG3 , RASGRF1 , ZIM2 , and ZNF215-- and range of cattle performance traits; significant associations ( P ≤ 0.05) were not observed between performance traits and SNPs within the PHLDA2 and TSPAN32 genes, although one SNP within the bovine TSPAN32 gene showed a tendency to be associated ( P ≤ 0.10) with a number of the performance traits assessed.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been suggested that animals grazing in areas near incineration plants might be exposed to high amounts of environmental pollutants with endocrine disrupting properties (Ingelido et al 2009). In countries practicing the spreading of sewage sludge on pastures, concentrations of endocrine disrupting chemicals were analysed in cattle and sheep and regarded to be too low to impair reproductive performance (Petro et al 2010; Rhind et al 2010). Similarly, in a large survey in Sweden in the pig, which is often fed processed food and thereby at risk of eating chemical pollutants that have been biomagnified, the burden of organochlorine contaminants at slaughter was found to be close to the detection limit of the analytical methods used (Glynn et al 2009).…”
Section: Endocrine Disruption and Reproduction In Farm Animals – Clinmentioning
confidence: 99%
“…In sheep, organs affected by pollutant exposure include the ovary, testis, hypothalamus and pituitary gland and bone. Reported effects of exposure include changes in organ weight and gross structure, histology and gene and protein expression [Rhind et al, 2010a]. Although this physiological insult has not yet been shown to lead to a reduction in ruminant gross performance, there are already reports indicating that EDC exposure can compromise several physiological systems and may pose a significant threat to both reproductive performance and welfare in the longer term.…”
Section: Endocrine-disrupting Compounds and Developmentmentioning
confidence: 99%
“…At present, many potential mechanisms of action for individual chemicals have been identified, but knowledge of factors affecting the rate of tissue exposure and of the effects of combinations of chemicals on physiological systems is poor. Nevertheless, both are vital for the identification of risks to animal productivity and welfare [Rhind et al, 2010a]. The effects of an EDC are variable across the life cycle of an animal, and are particularly potent when exposure occurs during fetal and early postnatal development.…”
Section: Endocrine-disrupting Compounds and Developmentmentioning
confidence: 99%
See 1 more Smart Citation